Sublimação Da Lógica E Atividade Filosófica: Uma Leitura Dos §§89-133 Das Investigações Filosóficas De Wittgenstein - Aquino, Fernando Lopes De [UNIFESP] (2018)
One Of The Main Objectives Of Philosophical Investigations Is To Try To Reorient The Use Of Philosophical Terms That Supposedly Evidence Something Essential Such As Proposition, Name, Thought, Language, World, Etc., From The Language Game In Which They Are Actually Used. The Result Of This Proposal Is None Other Than The Explanation Of A Series Of Illusions, Generated When Philosophers Sublimate A Certain "Form Of Representation" And Withdraw These Terms From The "Rough Soil" In Which They Stand. The Paragraphs 89-133, Traditionally Known As The Only Methodological Discussion Of The Investigations, Is One Of The Book's Clipping That Most Enables Us To Problematize This Discussion. The Intention Of This Research Is To Circumscribe These Questions, Taking Into Account Both The Comments Produced Around These Paragraphs And The Dynamics From Which The Texts Of The Investigations Were Produced. This Course Makes It Possible To Construct A View On Wittgensteinian Reflection On The Still More Radical Language Than M